Kemampuan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 1 Sumber Jaya Lampung Barat - Permanasari, Dian (JURNAL PESONA, 2017)
AbstractÂ The purpose of the research is to know and describe the students ability and the obstacles that students experience in writing the description text. The research method used is a quantitative descriptive method. The population of this study is the students of class VII which amounted to 296. The sample of this study as many as 30 students. The sampling technique uses Stratified Proportional Random Sampling. The main technique is to use assignment technique to get the student ability data in writing the description text. The results showed that the ability to write a description text has a value of 72.33 from and got enough category. In the aspect of the title reaching an average of 79.8, the opening aspect reaches an average of 88.7, the content aspect reaches an average of 78.53, the cover aspect reaches an average of 56.2, the vocabulary aspect reaches the average, Average of 70.53, the sentence structure aspect reaches the value of 62.7 and on the aspect of the EBI General Guidelines reaches a value of 50.57. So the lowest aspect in writing the description text is the average cover aspect that is 56.2 and the highest aspect in writing the description text are the opening aspects which reach an average of 88.7.Keyword: writing ability, descriptive text